CMOS Integrable CuO Nanowire Array Gas Sensors Enhanced by Au - Nanoparticles for Humidity Independent Gas Sensing. (2017) - Wimmer-Teubenbacher, Robert; Krainer, Johanna; Lackner, Eva; Sosada-Ludwikowska, Florentyna; Rohracher, Karl; Wachmann, Ewald; Poulsen, Katharina; Niehaus, Jan-Steffen; Köck, Anton
Abstract: CuO nanowire arrays, synthesized on chip, were evaluated for their gas sensing capabilities. The gas sensors were fabricated on test structures containing gold electrodes for conductometric measurement, a resistive heater and a thermocouple for proper temperature control. The initial metal structure was fabricated by electron beam lithography, thermal evaporation and lift-off process. In a consecutive step the metal structure is thermally oxidized at a temperature of 400°C. As a result of the temperature treatment nanowire growth is promoted during the thermal oxidation process. A CuO nanowire array is formed. This nanowire array is evaluated for carbon monoxide, - and a hydrocarbon-mixture (acetylene, ethane, ethene, and propene) for VOC testing at three relative humidity levels.